Optimization of metal barrier layers for enhanced SOI-based Ge PIN photodetector performance - Xu, Hanyuan (Nanyang Technological University, 2025)
This thesis investigates the optimization of titanium disilicide (TiSi₂) as a metal barrier layer for germanium PIN photodetectors on silicon-on-insulator (SOI) substrates to enhance their performance in high-speed optical communication systems. The study highlights the limitations of tantalum nitride (TaN) in high-speed applications and explores the potential of TiSi₂ in reducing contact resistance and improving device efficiency. Using the Design of Experiments (DOE) methodology, the research systematically evaluates the effects of critical process parameters—titanium layer thickness, annealing temperature, and annealing time on the electrical and optical properties of photodetectors have been investigated.